Single-crystal positive electrode material, preparation method thereof and positive plate

By selecting suitable doping elements M, N and L in a single crystal positive electrode material and controlling their ion radius and valence state, the problems of uneven morphology, poor dispersion and insufficient structural stability of the material are solved, and the uniformity, dispersion and electrochemical performance of the material are improved.

CN119725472APending Publication Date: 2025-03-28NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411931678.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the synthesis process, existing single-crystal positive electrode materials have problems such as uneven morphology, poor dispersion and insufficient structural stability, resulting in a degradation of electrochemical performance.

Method used

By selecting suitable doping elements M, N and L, controlling their ion radius, valence state and doping amount, ensuring uniform growth of single crystal positive electrode materials in all directions, and improving their structural stability and dispersion. The combination of M elements and L elements can maintain the stability and morphology of the material, and reduce contact between the materials through surface segregation, thereby improving dispersion.

Benefits of technology

The uniform morphology, high dispersion and structural stability of the single crystal positive electrode material are achieved, thereby improving the electrochemical performance and cyclic stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725472A_ABST
    Figure CN119725472A_ABST
Patent Text Reader

Abstract

The invention relates to a single-crystal positive electrode material, a preparation method thereof and a positive plate, the single-crystal positive electrode material is a high-nickel single-crystal positive electrode material comprising doping elements M, N and L. The ion radiuses, valence states and doping amounts of the doping elements M, N and L and Ni < 3 + > ions simultaneously meet the following relations: rM + rN is less than 1.5 rL, zM + zL is less than or equal to zN, and QM + QN is less than 1.5 QL. According to the preparation method, M, N and L are selected through specific ion radius, valence state and doping amount, so that the effect of improving the uniformity and dispersity of the single-crystal positive electrode material can be achieved, and the single-crystal positive electrode material also has relatively good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries and relates to a high-nickel positive electrode material, in particular to a single crystal positive electrode material and a preparation method and a positive electrode sheet thereof. Background Art

[0002] With the widespread popularity of new energy electric vehicles, higher requirements are placed on the cruising range and service life of electric vehicles. The cruising range and service life are closely related to the capacity and cycle performance of the material. Generally, increasing the nickel content and charging cut-off voltage of the material will increase the capacity of the material, but both of these will cause great damage to the structural stability of the material, causing the battery's cycle performance to drop sharply.

[0003] Since the structure of single crystal positive electrode materials is more complete and simpler than that of polycrystalline materials, and there are no grain boundaries inside the materials, cracks and side reactions can be effectively suppressed, thereby improving the electrochemical performance of the materials. However, single crystal materials require higher temperatures during the synthesis process, and the agglomeration and agglomeration of the materials are very serious, and usually require measures such as rolling and crushing to separate them. Although the materials are separated after rolling and crushing, due to the uneven internal stress of the materials during the synthesis process, the shapes after crushing are usually irregular, and the materials have many edges and corners, which are easy to break during the rolling process of the positive electrode sheet, thus affecting the performance of the materials.

[0004] Therefore, there is an urgent need to provide a single crystal positive electrode material with uniform morphology, high degree of dispersion, stable structure and good electrochemical performance, and a preparation method and positive electrode sheet thereof. Summary of the invention

[0005] The object of the present invention is to provide a single crystal positive electrode material and a preparation method and a positive electrode sheet thereof. The single crystal positive electrode material can select suitable M, N and L by specific ion radius and valence state, so as to ensure that the single crystal positive electrode material grows uniformly in all directions and has uniform morphology; the M element and the L element can maintain the stability and morphology of the single crystal positive electrode material, and the L element will gradually segregate to the surface of the single crystal positive electrode material during the preparation process, thereby reducing the contact between materials and improving the dispersibility of the single crystal positive electrode material.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a single crystal positive electrode material, wherein the single crystal positive electrode material is a high nickel single crystal positive electrode material including doping elements M, N and L.

[0008] In the single crystal positive electrode material, the ionic radius, valence state and doping amount of the doping elements M, N and L are similar to those of Ni 3+ The ions also satisfy the following relationship:

[0009] △r M +△rN <1.5△r L

[0010] △z M +△z L ≤△z N

[0011] Q M +Q N <1.5Q L

[0012] Among them, △r M is the absolute value of the difference between the ionic radius of M and the ionic radius of Ni, △r N is the absolute value of the difference between the ionic radius of N and the ionic radius of Ni, △r L is the absolute value of the difference between the ionic radius of L and the ionic radius of Ni. The unit of ionic radius is △z M is the valence state of the M element and Ni 3+ The absolute value of the difference in ion valence, △z N is the valence state of N element and Ni 3+ The absolute value of the difference in ion valence, △z L is the valence state of the L element and Ni 3+ The absolute value of the difference in ion valence; Q M is the mass content of M in the single crystal positive electrode material, Q N is the mass content of N in the single crystal cathode material, Q L is the mass content of L in the single crystal positive electrode material, and the unit of mass content is ppm.

[0013] High nickel single crystal positive electrode materials (Ni atomic percentage is more than 50%) have the problem of poor uniformity and dispersibility. The present invention selects doping elements with different effects through the relationship between the ion radius and valence state of the doping element and the matrix element; wherein the valence state and ion radius of the M element are relatively small, and it can be doped into the bulk phase of the high nickel positive electrode material to improve the structural stability of the material, and has little effect on the morphology of the material; the valence state of the N element is relatively high, and it has a higher bond energy with the oxygen element, which can improve the structural stability and change the surface energy of the material, so that the material grows uniformly along each crystal plane during the growth process, and the roundness and uniformity of the material are improved; however, because the M and N elements enhance the structural stability of the material, It affects the diffusion of lithium ions. If the doping amount is too much, it will reduce the capacity of the positive electrode material. The L element has a large ionic radius, which will promote the growth of the material during the sintering process. Combining with the N element will further improve the roundness and uniformity of the material. The ionic radius of the L element and the Ni element is quite different. It is difficult to dope into the bulk phase of the material during sintering. It will gradually segregate to the surface. A certain amount is required to form a uniform coating on the surface, which reduces the contact between the crystal planes and improves the dispersion of the material. The bond energy between the M, N and L elements and oxygen is stronger than the nickel-oxygen bond. The synergistic doping improves the structural stability. Moreover, the improvement of uniformity and dispersion promotes the separation of uniformity and reduces agglomeration, which improves the cycle stability of the single crystal positive electrode material. Therefore, the coordination of the M, N and L elements that satisfies the above relationship can improve the uniformity and dispersion of the single crystal positive electrode material and also has good electrochemical performance.

[0014] Preferably, the M includes any one of Al, Mg, Ti, Zr, Cr or Sn, or a combination of at least two of them.

[0015] Preferably, the N includes any one of Ta, Mo, Nb, W or Te, or a combination of at least two thereof.

[0016] Preferably, L includes any one of In, Sr, Bi or Ce, or a combination of at least two of them.

[0017] Preferably, Q M The value of satisfies 500ppm≤Q M ≤1500ppm.

[0018] Preferably, Q N The value of satisfies 500ppm≤Q N ≤1200ppm.

[0019] Preferably, Q L The value of satisfies 3000ppm≤Q L ≤6000ppm.

[0020] Preferably, the particle size D10 of the single crystal positive electrode material is 2 μm-4 μm, the particle size D50 is 4 μm-8 μm, and the particle size D90 is 7 μm-15 μm.

[0021] Preferably, the dispersion degree of the single crystal positive electrode material satisfies: D10 <0.5, f D50 <1.5 and f D90 <2.

[0022] Preferably, the particle size distribution Span value of the single crystal positive electrode material is 0.8-1.5.

[0023] Preferably, the roundness y of the single crystal positive electrode material is greater than 0.85, and the proportion q of the number of single crystal particles with a sphericity less than 0.7 in the whole is 0.7 <10%.

[0024] In a second aspect, the present invention provides a method for preparing a single crystal positive electrode material, the preparation method comprising the following steps:

[0025] The positive electrode material precursor, lithium source, M source, N source and L source are mixed according to the formula, and the obtained mixture is subjected to the first sintering, the second sintering and the third sintering in an oxygen-containing atmosphere in sequence to obtain the single crystal positive electrode material described in the first aspect.

[0026] The second sintering temperature>the third sintering temperature>the first sintering temperature.

[0027] The first sintering time>the second sintering time>the third sintering time.

[0028] The preparation method provided by the present invention firstly preheats the lithium source under a first sintering condition at a relatively low temperature to dehydrate the lithium source and fully contact the lithium source with the precursor, thereby improving the reaction activity of the lithium source and reducing the situation where the single crystal material lacks lithium internally due to its large size; then, fully reacts under a second sintering condition at a relatively high temperature; and finally, under a third sintering condition, the mixing of Li and Ni and oxygen vacancies are alleviated, so that multi-element doping can be doped into their respective positions, thereby ensuring the synergistic effect of M, N and L.

[0029] Preferably, the first sintering is performed at a temperature of 300° C.-500° C. and for a time of 8 h-12 h.

[0030] Preferably, the second sintering is performed at a temperature of 800° C.-1000° C. and for a time of 6 h-10 h.

[0031] Preferably, the third sintering is performed at a temperature of 700° C.-850° C. and for a time of 4 h-8 h.

[0032] Preferably, the M source comprises an M-containing oxide.

[0033] Preferably, the N source includes a N-containing oxide.

[0034] Preferably, the L source includes an L-containing oxide.

[0035] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active material disposed on at least one side surface of the current collector.

[0036] The positive electrode active material includes the single crystal positive electrode material described in the first aspect; or includes the single crystal positive electrode material prepared by the preparation method described in the second aspect.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention selects doping elements with different effects through the relationship between the ion radius and valence state of the doping element and the matrix element; the valence state and ion radius of the M element are relatively small, and it can be doped into the bulk phase of the high-nickel positive electrode material to improve the structural stability of the material, and has little effect on the morphology of the material; the valence state of the N element is relatively high, and it has a higher bond energy with the oxygen element, which can improve the structural stability and change the surface energy of the material, so that the material grows uniformly along each crystal plane during the growth process, and the roundness and uniformity of the material are improved; however, because the M and N elements enhance the structural stability of the material, they will affect the diffusion of lithium ions, and if the doping amount is too much, it will reduce The capacity of the positive electrode material; the L element has a large ionic radius, which will promote the growth of the material during the sintering process. Combining with the N element will further improve the roundness and uniformity of the material. The ionic radius of the L element and the Ni element is quite different, so it is difficult to dope into the bulk phase of the material during sintering. It will gradually segregate to the surface, and a certain amount is required to form a uniform coating on the surface, which reduces the contact between the crystal planes and improves the dispersion of the material; the bond energy between the M, N and L elements and oxygen is stronger than the nickel-oxygen bond, and the synergistic doping improves the structural stability. Moreover, the improvement in uniformity and dispersion promotes the separation of uniformity and reduces agglomeration, which improves the cycle stability of the single crystal positive electrode material. Therefore, the coordination of the M, N and L elements that satisfies the above relationship can play a role in improving the uniformity and dispersion of the single crystal positive electrode material, and also has good electrochemical performance.

[0039] (2) The preparation method provided by the present invention first preheats under a first sintering condition at a relatively low temperature to dehydrate the lithium source and fully contact it with the precursor, thereby improving the reactivity of the lithium source and reducing the situation where the single crystal material lacks lithium internally due to its large size; then fully reacts under a second sintering condition at a relatively high temperature; and finally, under a third sintering condition, alleviates the mixing of Li and Ni and oxygen vacancies, so that multi-element doping can be doped into their respective positions, thereby ensuring the synergistic effect of M, N and L. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the SEM image of the single crystal positive electrode material obtained in Example 1.

[0041] Figure 2 This is a test diagram of the roundness of the single crystal positive electrode material obtained in Example 1.

[0042] Figure 3 This is the SEM image of the single crystal positive electrode material obtained in Example 16.

[0043] Figure 4 This is a test diagram of the roundness of the single crystal positive electrode material obtained in Example 16. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] The present invention provides a single crystal positive electrode material, wherein the single crystal positive electrode material is a high-nickel single crystal positive electrode material comprising doping elements M, N and L.

[0046] The ionic radius, valence state and doping amount of doping elements M, N, L and Ni 3+ The ions also satisfy the following relationship: △r M +△r N <1.5△r L , △z M +△z L ≤△z N , Q M +Q N <1.5Q L .

[0047] Among them, △r M The ionic radius of M and Ni 3+ The absolute value of the difference in ionic radius, △r N is the ionic radius of N and Ni 3+ The absolute value of the difference in ionic radius, △r L The ionic radius of L is the same as that of Ni 3+ The absolute value of the difference in ionic radius; △z M is the valence state of the M element and Ni 3+ The absolute value of the difference in ion valence, △z N is the valence state of N element and Ni 3+ The absolute value of the difference in ion valence, △z L is the valence state of the L element and Ni 3+ The absolute value of the difference in ion valence; Q M is the mass content of M in the single crystal positive electrode material, Q Nis the mass content of N in the single crystal cathode material, Q L is the mass content of L in the single crystal positive electrode material.

[0048] High nickel single crystal positive electrode materials have the problem of poor uniformity and dispersibility. The present invention selects doping elements with different effects through the relationship between the ion radius and valence state of the doping elements and the matrix elements; among them, the valence state and ion radius of the M element are relatively small, and it can be doped into the bulk phase of the high nickel positive electrode material to improve the structural stability of the material, and has little effect on the morphology of the material; the valence state of the N element is relatively high, and it has a higher bond energy with the oxygen element, which can improve the structural stability and change the surface energy of the material, so that the material grows uniformly along each crystal plane during the growth process, and the roundness and uniformity of the material are improved; however, because the M and N elements enhance the structural stability of the material, they will affect the diffusion of lithium ions. , if the doping amount is too much, the capacity of the positive electrode material will be reduced; the L element has a large ionic radius, which will promote the growth of the material during the sintering process, and the combination with the N element will further improve the roundness and uniformity of the material. The ionic radius of the L element and the Ni element is quite different, so it is difficult to dope into the bulk phase of the material during sintering. It will gradually segregate to the surface, and a certain amount is required to form a uniform coating on the surface, which reduces the contact between the crystal planes and improves the dispersion of the material; the bond energy between the M, N and L elements and oxygen is stronger than the nickel-oxygen bond, and the synergistic doping improves the structural stability. Moreover, the improvement of uniformity and dispersion promotes the separation of uniformity and reduces agglomeration, and improves the cycle stability of the single crystal positive electrode material. Therefore, the coordination of the M, N and L elements that satisfies the above relationship can play a role in improving the uniformity and dispersion of high-nickel single crystal positive electrode materials, and also has good electrochemical properties.

[0049] In certain embodiments, M includes any one of Al, Mg, Ti, Zr, Cr or Sn, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of Al and Mg, a combination of Mg and Ti, a combination of Zr and Cr, a combination of Cr and Sn, a combination of Al, Mg and Ti, a combination of Zr, Cr and Sn, or a combination of Al, Mg, Ti, Zr, Cr and Sn.

[0050] In some embodiments, the N includes any one of Ta, Mo, Nb, W or Te, or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ta and Mo, a combination of Nb and W, a combination of W and Te, a combination of Ta, Mo and Nb, a combination of Nb, W and Te, or a combination of Ta, Mo, Nb, W and Te.

[0051] In some embodiments, L includes any one of In, Sr, Bi or Ce or a combination of at least two of them. Typical but non-limiting combinations include a combination of In and Sr, a combination of Bi and Ce, a combination of Sr and Bi, or a combination of In, Sr, Bi and Ce.

[0052] In certain embodiments, Q M The value of satisfies 500ppm≤Q M ≤1500ppm, for example, it can be 500ppm, 600ppm, 800ppm, 1000ppm, 1200ppm or 1500ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In certain embodiments, Q N The value of satisfies 500ppm≤Q N ≤1200ppm, for example, it can be 500ppm, 600ppm, 800ppm, 900ppm, 1000ppm or 1200ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In certain embodiments, Q L The value of satisfies 3000ppm≤Q L ≤6000ppm, for example, it can be 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm or 6000ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In the single crystal positive electrode material provided by the present invention, the content of M in the single crystal positive electrode material is less than the content of L in the single crystal positive electrode material; the content of N in the single crystal positive electrode material is less than the content of L in the single crystal positive electrode material.

[0056] In some embodiments, the particle size D10 of the single crystal positive electrode material is 2 μm-4 μm, the particle size D50 is 4 μm-8 μm, and the particle size D90 is 7 μm-15 μm.

[0057] The particle size D10 of the single crystal positive electrode material is 2 μm-4 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0058] The particle size D50 of the single crystal positive electrode material is 4 μm-8 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0059] The particle size D90 of the single crystal positive electrode material is 7 μm-15 μm, for example, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm or 15 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0060] In some embodiments, the dispersion degree of the single crystal positive electrode material satisfies: D10 <0.5, f D50 <1.5 and f D90 <2.

[0061] In the present invention, the dispersion degree of the single crystal positive electrode material refers to: directly testing the particle size of the single crystal positive electrode material to obtain D 内10 , D 内50 With D 内90 The single crystal cathode material was ultrasonically dispersed in deionized water for 45 seconds, with lithium hexafluorophosphate as the dispersant, and then added dropwise to the particle size test device for testing to obtain D 外10 , D 外50 With D 外90 , then f D10 =D 外10 -D 内10 , f D50 =D 外50 -D 内50 , f D90 =D 外90 -D 内90 .f D10 、f D50 With f D90 The closer the value is to 0, the higher the dispersion.

[0062] In some embodiments, the particle size distribution Span value of the single crystal positive electrode material is 0.8-1.5, for example, it can be 0.8, 0.9, 1, 1.2, 1.3 or 1.5, but it is not limited to the listed values, and the remaining values ​​not listed in the numerical range are also applicable. The smaller the particle size distribution Span value, the narrower the particle size distribution.

[0063] In some embodiments, the roundness y of the single crystal positive electrode material is greater than 0.85, and the proportion q of the number of single crystal particles with a sphericity less than 0.7 in the whole is 0.7 <10%.

[0064] In the present invention, the roundness is obtained by performing SEM testing on the single crystal positive electrode material. The specific test is as follows: the area of ​​each single crystal particle in the SEM image is calculated to obtain the comparative circle diameter D1 and the minimum circumscribed circle diameter D2, then the sphericity q = D1 / D2, the sphericity of at least 200 single crystal particles is counted, and the average value is taken to obtain the roundness y of the single crystal positive electrode material. Note: The range of the roundness is 0 to 1, and the closer to 1, the better the roundness.

[0065] A certain embodiment of the present invention provides a method for preparing a single crystal positive electrode material, the preparation method comprising the following steps:

[0066] The positive electrode material precursor, lithium source, M source, N source and L source are mixed according to the formula, and the obtained mixture is subjected to a first sintering, a second sintering and a third sintering in an oxygen-containing atmosphere in sequence to obtain the single crystal positive electrode material described in any embodiment.

[0067] The second sintering temperature>the third sintering temperature>the first sintering temperature.

[0068] The first sintering time>the second sintering time>the third sintering time.

[0069] The preparation method provided by the present invention firstly preheats the lithium source under a first sintering condition at a relatively low temperature to dehydrate the lithium source and fully contact the lithium source with the precursor, thereby improving the reaction activity of the lithium source and reducing the situation where the single crystal material lacks lithium internally due to its large size; then, fully reacts under a second sintering condition at a relatively high temperature; and finally, under a third sintering condition, the mixing of Li and Ni and oxygen vacancies are alleviated, so that multi-element doping can be doped into their respective positions, thereby ensuring the synergistic effect of M, N and L.

[0070] The oxygen-containing atmosphere of the present invention includes but is not limited to oxygen atmosphere.

[0071] In certain embodiments, the lithium source includes lithium hydroxide.

[0072] In some embodiments, the first sintering is performed at a temperature of 300° C.-500° C. and for a time of 8 h-12 h.

[0073] The temperature of the first sintering is 300° C.-500° C., for example, 300° C., 350° C., 400° C., 450° C. or 500° C., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0074] The first sintering time is 8 h-12 h, for example, 8 h, 9 h, 10 h, 11 h or 12 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0075] In some embodiments, the second sintering is performed at a temperature of 800° C.-1000° C. and for a time of 6 h-10 h.

[0076] The temperature of the second sintering is 800°C-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0077] The second sintering time is 6 h-10 h, for example, 6 h, 7 h, 8 h, 9 h or 10 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0078] In some embodiments, the third sintering is performed at a temperature of 700° C.-850° C. and for a time of 4 h-8 h.

[0079] The temperature of the third sintering is 700°C-850°C, for example, it can be 700°C, 720°C, 750°C, 780°C, 800°C, 820°C or 850°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0080] The third sintering time is 4 hours to 8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0081] In certain embodiments, the M source includes an M-containing oxide.

[0082] In some embodiments, the N source includes a N-containing oxide.

[0083] In certain embodiments, the L source includes an L-containing oxide.

[0084] The present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active material arranged on at least one side surface of the current collector.

[0085] The positive electrode active material includes the single crystal positive electrode material described in any embodiment; or includes the single crystal positive electrode material prepared by the preparation method described in any embodiment.

[0086] In some embodiments, the ultimate compaction density of the positive electrode sheet is not less than 3.8 g / cm 3 .

[0087] Example 1

[0088] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0089] (1) Evenly mix the cathode material precursor Ni 0.83 Co0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0090] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0091] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0092] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0093] (4) In an oxygen atmosphere, the temperature was lowered to 800°C, kept at this temperature for 6 hours, and naturally cooled to obtain a single crystal positive electrode material. The SEM image of the obtained single crystal positive electrode material is shown in FIG. Figure 1 shown.

[0094] Depend on Figure 1 and Figure 2 It can be seen that the single crystal positive electrode material prepared in this embodiment has good uniformity, dispersibility and high roundness.

[0095] Example 2

[0096] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0097] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 、MoO 3 and CeO 2 , get the mixed amount.

[0098] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 、MoO 3 and CeO 2The dosage is such that the mass contents of Al, Mo and Ce in the single crystal positive electrode material are 1000ppm, 1000ppm and 4000ppm respectively.

[0099] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0100] (3) In an oxygen atmosphere, the temperature was further increased to 925°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0101] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0102] Example 3

[0103] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0104] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, ZrO 2 、MoO 3 and SrO to obtain a mixed amount.

[0105] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; ZrO 2 、MoO 3 The dosage of and SrO makes the mass contents of Zr, Mo and Sr in the single crystal positive electrode material 1200ppm, 1000ppm and 4000ppm respectively.

[0106] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0107] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0108] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0109] Example 4

[0110] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0111] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, MgO, MoO3 and SrO to obtain a mixed amount.

[0112] The molar ratio of lithium hydroxide to cathode material precursor is 1.05:1; MgO, MoO 3 The dosage of and SrO makes the mass contents of Mg, Mo and Sr in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0113] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0114] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0115] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0116] Example 5

[0117] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0118] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0119] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0120] (2) In an oxygen atmosphere, heat the sample to 300°C at a rate of 2°C / min and keep the temperature for 12 h.

[0121] (3) In an oxygen atmosphere, continue to increase the temperature to 800°C at a heating rate of 2°C / min and keep it at this temperature for 10 h.

[0122] (4) In an oxygen atmosphere, the temperature is lowered to 700° C., kept at this temperature for 8 h, and naturally cooled to obtain a single crystal positive electrode material.

[0123] Example 6

[0124] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0125] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0126] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0127] (2) In an oxygen atmosphere, heat the sample to 500°C at a rate of 2°C / min and keep the temperature for 8 h.

[0128] (3) In an oxygen atmosphere, continue to increase the temperature to 1000°C at a heating rate of 2°C / min and keep it at that temperature for 6 h.

[0129] (4) Under an oxygen atmosphere, the temperature was lowered to 850° C., kept at this temperature for 4 h, and naturally cooled to obtain a single crystal positive electrode material.

[0130] Example 7

[0131] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0132] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0133] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 500ppm, 500ppm and 3000ppm respectively.

[0134] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0135] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0136] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0137] Example 8

[0138] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0139] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0140] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1500ppm, 1200ppm and 6000ppm respectively.

[0141] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0142] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0143] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0144] Example 9

[0145] This embodiment provides a single crystal positive electrode material, in addition to controlling Al 2 O 3Except for the amount of Al used to make the mass content of Al in the single crystal positive electrode material 400ppm, the rest is the same as Example 1.

[0146] Example 10

[0147] This embodiment provides a single crystal positive electrode material, in addition to controlling Al 2 O 3 Except for the amount of , the mass content of Al in the single crystal positive electrode material is 1600ppm, the rest is the same as Example 1.

[0148] Embodiment 11

[0149] This embodiment provides a single crystal positive electrode material, in addition to controlling MoO 3 Except for the amount of Mo used to make the mass content of Mo in the single crystal positive electrode material 400ppm, the rest is the same as Example 1.

[0150] Example 12

[0151] This embodiment provides a single crystal positive electrode material, in addition to controlling MoO 3 Except for the amount of Mo used to make the mass content of Mo in the single crystal positive electrode material 1500ppm, the rest is the same as Example 1.

[0152] Embodiment 13

[0153] This embodiment provides a single crystal positive electrode material. In addition to controlling CeO 2 Except for the amount of Ce used to make the mass content of Ce in the single crystal positive electrode material 2500ppm, the rest is the same as Example 1.

[0154] Embodiment 14

[0155] This embodiment provides a single crystal positive electrode material. In addition to controlling CeO 2 Except for the amount of Ce used to make the mass content of Ce in the single crystal positive electrode material 6500ppm, the rest is the same as Example 1.

[0156] Embodiment 15

[0157] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0158] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0159] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0160] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 8 h.

[0161] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0162] (4) In an oxygen atmosphere, the temperature was lowered to 800°C, kept at this temperature for 8 h, and cooled naturally to obtain a single crystal positive electrode material.

[0163] Example 16

[0164] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0165] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and ZrO 2 , get the mixed amount.

[0166] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and ZrO 2 The dosage is such that the mass contents of Al, Nb and Zr in the single crystal positive electrode material are 1000ppm, 1000ppm and 4000ppm respectively.

[0167] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0168] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0169] (4) In an oxygen atmosphere, the temperature was lowered to 800°C, kept at this temperature for 6 hours, and naturally cooled to obtain a single crystal positive electrode material. The SEM image of the obtained single crystal positive electrode material is shown in FIG. Figure 3 shown.

[0170] Depend on Figure 3 and Figure 4 It can be seen that since the L element in this comparative example is Zr, the uniformity and dispersion of the single crystal positive electrode material finally obtained by combining M, N and L elements are poor, and the overall roundness is not high; Figure 1 In comparison, the Zr element with a smaller ionic radius and valence state selected in this comparative example cannot play a role in promoting material growth during the sintering process, nor can it be combined with the N element to improve the roundness and uniformity of the single crystal positive electrode material, nor can it form a uniform protective layer on the surface of the material. The single crystal positive electrode material obtained in Example 1 is prepared by controlling the M, N and L doping elements and doping amounts to prepare a single crystal positive electrode material with a more uniform morphology and roundness, thereby having a higher capacity and better cycle performance.

[0171] Embodiment 17

[0172] This embodiment provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0173] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0174] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 2000ppm, 1500ppm and 2500ppm respectively.

[0175] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0176] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0177] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0178] Comparative Example 1

[0179] This comparative example provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0180] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 and lithium hydroxide to obtain a mixed amount.

[0181] The molar ratio of lithium hydroxide to the positive electrode material precursor is 1.05:1.

[0182] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0183] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0184] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0185] Comparative Example 2

[0186] This comparative example provides a single crystal positive electrode material, and the single crystal positive electrode material is prepared without first sintering, and includes the following steps:

[0187] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0188] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0189] (2) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0190] (3) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0191] Comparative Example 3

[0192] This comparative example provides a single crystal positive electrode material, and the preparation of the single crystal positive electrode material is performed without performing the third sintering, and includes the following steps:

[0193] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and CeO 2 , get the mixed amount.

[0194] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb 2 O 5 and CeO 2 The dosage makes the mass contents of Al, Nb and Ce in the single crystal positive electrode material 1000ppm, 1000ppm and 4000ppm respectively.

[0195] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0196] (3) In an oxygen atmosphere, the temperature is further increased to 930° C. at a heating rate of 2° C. / min, kept at this temperature for 14 h, and naturally cooled to obtain a single crystal positive electrode material.

[0197] Comparative Example 4

[0198] This comparative example provides a single crystal positive electrode material, and the preparation method includes the following steps:

[0199] (1) Evenly mix the cathode material precursor Ni 0.83 Co 0.06 Mn 0.11 (OH) 2 , lithium hydroxide, Al 2 O 3 , Nb 2 O 5 and ZrO 2 , get the mixed amount.

[0200] The molar ratio of lithium hydroxide to the cathode material precursor is 1.05:1; Al 2 O 3 , Nb2 O 5 and WO 3 The dosage is such that the mass contents of Al, Nb and Zr in the single crystal positive electrode material are 1000ppm, 1000ppm and 4000ppm respectively.

[0201] (2) In an oxygen atmosphere, heat the sample to 400°C at a rate of 2°C / min and keep the temperature for 10 h.

[0202] (3) In an oxygen atmosphere, the temperature was further increased to 930°C at a heating rate of 2°C / min and kept at this temperature for 8 h.

[0203] (4) In an oxygen atmosphere, the temperature is lowered to 800° C., kept at this temperature for 6 h, and naturally cooled to obtain a single crystal positive electrode material.

[0204] Performance Testing

[0205] The positive electrode materials, conductive carbon black, and binder polyvinylidene fluoride obtained in the above-mentioned embodiments and comparative examples are weighed in a mass ratio of 95:3:2, and are fully stirred and mixed in an N-methylpyrrolidone solvent to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil, and after drying and cold pressing, a positive electrode sheet including a positive electrode active layer with a thickness of 100 μm is obtained; the positive electrode sheet, a lithium sheet, a polyethylene isolation film, and an electrolyte (the electrolyte is LiPF6, and the solvent is EC / DMC) are assembled into a button battery in a button box.

[0206] Under the condition of 0.2C constant current charging, the charging cut-off voltage is 4.3V. Then, constant voltage charging is performed under the cut-off voltage condition until the current is less than 0.05C. The charging capacity at this time is recorded as the first cycle charging capacity. After that, it is left to stand for 5 minutes and then discharged at 0.2C constant current to a voltage of 2.8V. The discharge capacity this time is recorded as the battery's first cycle discharge capacity, which is also the initial capacity.

[0207] According to the method of the buckle capacitance test, the positive electrode material is coated into a positive electrode sheet, and the negative electrode is made of graphite, and is combined with a diaphragm polyethylene and an electrolyte (the electrolyte is LiPF 6 The full battery was composed of EC / DMC (solvent), and cycled under the condition of charge and discharge rate of 1C. The capacity of each cycle was compared with the initial capacity to confirm the capacity retention rate; at 45°C, the capacity retention rate was calculated after 300 cycles.

[0208] The particle size was measured using a Malvern 3000 laser particle size tester.

[0209] The chemical composition of the positive electrode material was tested by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0210] Table 1

[0211] <![CDATA[r M ]]> M <![CDATA[Q M / ppm]]> <![CDATA[r N ]]> N <![CDATA[Q N / ppm]]> <![CDATA[r L ]]> L <![CDATA[Q L / ppm]]> Example 1 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 2 0.54 <![CDATA[Al 3+ ]]> 1000 0.59 <![CDATA[Mo 6+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 3 0.72 <![CDATA[Zr 4+ ]]> 1000 0.59 <![CDATA[Mo 6+ ]]> 1000 1.18 <![CDATA[Sr 2+ ]]> 4000 Example 4 0.72 <![CDATA[Mg 2+ ]]> 1000 0.59 <![CDATA[Mo 6+ ]]> 1000 1.18 <![CDATA[Sr 2+ ]]> 4000 Example 5 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 6 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 7 0.54 <![CDATA[Al 3+ ]]> 500 0.64 <![CDATA[Nb 5+ ]]> 500 1.14 <![CDATA[Ce 4+ ]]> 3000 Example 8 0.54 <![CDATA[Al 3+ ]]> 1500 0.64 <![CDATA[Nb 5+ ]]> 1200 1.14 <![CDATA[Ce 4+ ]]> 6000 Example 9 0.54 <![CDATA[Al 3+ ]]> 400 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 10 0.54 <![CDATA[Al 3+ ]]> 1600 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Embodiment 11 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 400 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 12 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1500 1.14 <![CDATA[Ce 4+ ]]> 4000 Embodiment 13 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 2500 Embodiment 14 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 6500 Embodiment 15 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Example 16 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 0.72 <![CDATA[Zr 4+ ]]> 4000 Embodiment 17 0.54 <![CDATA[Al 3+ ]]> 2000 0.64 <![CDATA[Nb 5+ ]]> 1500 1.14 <![CDATA[Ce 4+ ]]> 2500 Comparative Example 1 / / / / / / / / / Comparative Example 2 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Comparative Example 3 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 1.14 <![CDATA[Ce 4+ ]]> 4000 Comparative Example 4 0.54 <![CDATA[Al 3+ ]]> 1000 0.64 <![CDATA[Nb 5+ ]]> 1000 0.60 <![CDATA[W 6+ ]]> 4000

[0212] Table 2

[0213]

[0214]

[0215] Table 3

[0216] <![CDATA[D 10 ]]> <![CDATA[D 50 ]]> <![CDATA[D 90 ]]> <![CDATA[f D10 ]]> <![CDATA[f D50 ]]> <![CDATA[f D90 ]]> Span y <![CDATA[q 0.7 ]]> Example 1 2.5 5.5 7.2 0.36 0.81 1.34 0.85 0.895 4.35% Example 2 2.3 5.3 7.1 0.4 0.85 1.52 0.91 0.885 4.29% Example 3 2.6 5.6 8.2 0.37 0.82 1.33 1 0.883 5.55% Example 4 2.2 5.1 7 0.38 0.85 1.45 0.94 0.882 5.41% Example 5 2.1 4.5 7 0.34 0.9 1.46 1.09 0.888 4.86% Example 6 3.8 7.5 12 0.4 1.02 1.58 1.09 0.881 4.95% Example 7 2.6 5.8 8.5 0.38 1.01 1.67 1.02 0.867 6.50% Example 8 3.1 6.5 8.3 0.39 1.05 1.85 0.8 0.863 6.52% Example 9 2.49 5.48 7.18 0.35 0.8 1.35 0.86 0.878 5.62% Example 10 2.5 5.5 7.2 0.36 0.81 1.34 0.85 0.856 7.56% Embodiment 11 2.6 6.6 12 0.45 1 2.6 1.42 0.864 6.35% Example 12 1.5 4 7 0.5 1.1 2.7 1.38 0.876 6.15% Embodiment 13 2 4.5 8.5 0.5 1.2 2.65 1.44 0.880 4.59% Embodiment 14 2 8 15 0.7 1.85 2.5 1.63 0.858 7.84% Embodiment 15 2.2 4.45 8 0.65 1.67 2.53 1.3 0.825 8.89% Example 16 2.1 4.5 10.2 0.8 1.9 2.55 1.8 0.795 14.56% Embodiment 17 2 4.1 11.4 0.85 2 2.5 2.29 0.843 10.16% Comparative Example 1 1.9 4 10.3 0.75 2.3 2.56 2.1 0.815 12.78% Comparative Example 2 2 5 9.7 0.6 1.5 2.6 1.54 0.845 10.05% Comparative Example 3 2.17 8 18 0.6 2.5 2.78 1.98 0.835 10.23% Comparative Example 4 1.5 3.5 7 0.5 1.5 3 1.57 0.825 10.56%

[0217] Table 4

[0218]

[0219]

[0220] In summary, the present invention screens doping elements with different effects through the relationship between the ion radius and valence state of the doping element and the matrix element; the valence state and ion radius of the M element are relatively small, and it can be doped into the bulk phase of the high-nickel positive electrode material to improve the structural stability of the material, and has little effect on the morphology of the material; the valence state of the N element is relatively high, and it has a higher bond energy with the oxygen element, which can improve the structural stability and change the surface energy of the material, so that the material grows uniformly along each crystal plane during the growth process, and the roundness and uniformity of the material are improved; however, because the M and N elements enhance the structural stability of the material, they will affect the diffusion of lithium ions, and if the doping amount is too much, it will reduce The capacity of the low positive electrode material; the L element has a large ionic radius, which will promote the growth of the material during the sintering process, and the combination with the N element will further improve the roundness and uniformity of the material. The ionic radius of the L element and the Ni element is quite different, so it is difficult to dope into the bulk phase of the material during sintering. It will gradually segregate to the surface, and a certain amount is required to form a uniform coating on the surface, which reduces the contact between the crystal planes and improves the dispersion of the material; the bond energy between the M, N and L elements and oxygen is stronger than the nickel-oxygen bond, and the synergistic doping improves the structural stability. Moreover, the improvement in uniformity and dispersion promotes the separation of uniformity and reduces agglomeration, and improves the cycle stability of the single crystal positive electrode material. Therefore, the coordination of the M, N and L elements that satisfies the above relationship can play a role in improving the uniformity and dispersion of the single crystal positive electrode material, and also has good electrochemical performance.

[0221] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A single crystal positive electrode material, characterized in that: The single crystal positive electrode material is a high nickel single crystal positive electrode material including doping elements M, N and L; The ionic radius, valence state and doping amount of doping elements M, N, L and Ni 3+ The ions also satisfy the following relationship: △r M +△r N <1.5△r L , △z M +△z L ≤△z N , Q M +Q N <1.5Q L ; Among them, △r M is the absolute value of the difference between the ionic radius of M and the ionic radius of Ni, △r N is the absolute value of the difference between the ionic radius of N and the ionic radius of Ni, △r L is the absolute value of the difference between the ionic radius of L and the ionic radius of Ni; △z M is the valence state of the M element and Ni 3+ The absolute value of the difference in ion valence, △z N is the valence state of N element and Ni 3+ The absolute value of the difference in ion valence, △z L is the valence state of the L element and Ni 3+ The absolute value of the difference in ion valence; Q M is the mass content of M in the single crystal positive electrode material, Q N is the mass content of N in the single crystal cathode material, Q L is the mass content of L in the single crystal positive electrode material.

2. The single crystal positive electrode material according to claim 1, characterized in that: The M includes any one of Al, Mg, Ti, Zr, Cr or Sn, or a combination of at least two of them.

3. The single crystal positive electrode material according to claim 1, characterized in that: The N includes any one of Ta, Mo, Nb, W or Te, or a combination of at least two of them.

4. The single crystal positive electrode material according to claim 1, characterized in that: The L includes any one of In, Sr, Bi or Ce or a combination of at least two of them.

5. The single crystal positive electrode material according to any one of claims 1 to 4, characterized in that: Q M The value of satisfies 500ppm≤Q M ≤1500ppm, Q N The value of satisfies 500ppm≤Q N ≤1200ppm, Q L The value of satisfies 3000ppm≤Q L ≤6000ppm.

6. The single crystal positive electrode material according to claim 1, characterized in that: The particle size D10 of the single crystal positive electrode material is 2 μm-4 μm, the particle size D50 is 4 μm-8 μm, and the particle size D90 is 7 μm-15 μm; And / or, the dispersion degree of the single crystal positive electrode material satisfies: D10 <0.5, f D50 <1.5 and f D90 <2; And / or, the particle size distribution Span value of the single crystal positive electrode material is 0.8-1.5; And / or, the roundness y of the single crystal positive electrode material is greater than 0.85, and the proportion q of the number of single crystal particles with a sphericity less than 0.7 in the whole 0.7 <10%.

7. A method for preparing a single crystal positive electrode material, characterized in that: The preparation method comprises the following steps: A positive electrode material precursor, a lithium source, an M source, an N source and an L source are mixed according to a formula, and the obtained mixture is subjected to a first sintering, a second sintering and a third sintering in an oxygen-containing atmosphere in sequence to obtain the single crystal positive electrode material according to any one of claims 1 to 6; The temperature of the second sintering>the temperature of the third sintering>the temperature of the first sintering; The first sintering time>the second sintering time>the third sintering time.

8. The preparation method according to claim 7, characterized in that: The first sintering temperature is 300°C-500°C, and the time is 8h-12h; And / or, the second sintering temperature is 800°C-1000°C, and the time is 6h-10h; And / or, the third sintering is performed at a temperature of 700° C.-850° C. and for a time of 4 h-8 h.

9. The preparation method according to claim 7 or 8, characterized in that: The M source includes an oxide containing M; And / or, the N source includes an oxide containing N; And / or, the L source includes an L-containing oxide.

10. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and a positive electrode active material disposed on at least one side surface of the current collector; The positive electrode active material includes the single crystal positive electrode material according to any one of claims 1 to 6; or includes the single crystal positive electrode material prepared by the preparation method according to any one of claims 7 to 9.